Organogels Thermodynamics, Structure, Solvent Role, and Properties - Guenet, Jean-Michel (SpringerBriefs in Materials,, 2016)
This book provides a physics-oriented introduction to organogels with a comparison to polymer thermoreversible gels whenever relevant. The past decade has seen the development of a wide variety of newly-synthesized molecules that can spontaneously self-assemble or crystallize from their organic or aqueous solutions to produce fibrillar networks, namely organogels, with potential applications in organic electronics, light harvesting, bio-imaging, non-linear optics, and the like. This compact volume presents a detailed outlook of these novel molecular systems with special emphasis upon their thermodynamics, morphology, molecular structure, and rheology. The definition of these complex systems is also tackled, as well as the role of the solvent. The text features numerous temperature-phase diagrams for a variety of organogels as well as illustrations of their structures at the microscopic, mesoscopic and macroscopic level. A review of some potential applications is provided including hybrid functional materials with polymers and with carbon nanotubes. Throughout, discussions of theoretical developments and experimental advances are written at a level suitable for beginning graduate students through practicing researchers.